Disentangling the effects of domestic corporate political activity and political connections on firms' internationalisation: Evidence from US retail MNEs. Issue 1 (February 2022) - Shirodkar, Vikrant; Batsakis, Georgios; Konara, Palitha; Mohr, Alexander
Highlights: We study how firms' political activities and connections affect internationalization. We study this in the context of the retail-services industry of the United States. We find political activities to ease and connections to hinder internationalization. Product diversification and international experience moderate this relationship. We contribute to studies on firms political activities in international business. Abstract: Scholars are increasingly investigating the implications of firms' domestic corporate political activity (CPA) and political connections on their internationalisation prospects. In this paper, using insights from the resource dependence theory, we argue that domestic CPA and political connections developed within the home country have contrasting effects on firms' international expansion, such that, while domestic CPAs (mainly, lobbying and campaign contributions) facilitate internationalisation, political connections deter internationalisation. We also argue that this relationship is moderated by firms' international experience and product diversification. We test our hypotheses using a panel dataset comprising 38 retail Multinational Enterprises (MNEs) originating in the United States (US) whose activities we traced over the 16-year period 2003−2018. Our findings support our hypotheses.